SAHABAT BELAJAR, BUKAN MUSUH: MEMBANGUN BIMBINGAN BELAJAR YANG POSITIF DAN BEBAS BULLYING - ulya; Umi Fatihaturrohmah; Azza Roycha Amanda; Anisa Ayu Afsari; Elvira Sho’idatut Taqiyah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The mission of Higher Education is implemented in the Tridharma Perguruan Tinggi, namely education, research, and community service. Learning assistance is a crucial form of community service to improve children's achievement and motivation to learn. This program was carried out in Selojari Village, Klambu, Grobogan. The target of the activity is elementary school age children. The scope of the activity includes learning assistance and the implementation of the anti-bullying program. The participants of the program amounted to 25 children and it was carried out for 40 days. The results showed an increase in motivation and learning achievement. Most of the participants understood the material better, they showed enthusiasm for participating in tutoring activities with the indicator of the number of absences in the meeting was very minimal. They become more understanding of the material than just getting the material at school. Meanwhile, the implementation of the anti-bullying program also showed positive results, as seen from the increasingly harmonious friendship between them. Social relations between students become better, do not denounce each other, do not group, which causes quarrels. In general, the activity went well, smoothly, and contributively. However, several obstacles are faced, such as limited facilities, including lack of lighting and room comfort.